On the morphology of the digestive system of two monomorium ant species - Solis, Daniel Russ [UNESP]; Rossi, Mônica Lanzoni; Fox, Eduardo Gonçalves Paterso; Nogueira, Neusa De Lima; Tanaka, Francisco André Ossamu; Bueno, Odair Correa [UNESP] (Oxford University Press (OUP), 2013)
The digestive system of adults and mature larvae of two ant species of Monomorium Mayr (Hymoneptera: Formicidae) were described with the aid of light and scanning electron microscopy, as there is a lack of studies in this area. These two ant species are recurrently found in urban habitats and are known as 'tramp species,' as they cause problems in households, businesses, and hospitals. The most interesting finds of the present study include the existence of spinules in the crop of adults, and the number of Malpighian tubules and rectal pads was constant among different castes, ages, and species. © This is an open access paper.
Keywords: Formicidae; Monomorium floricola; Monomorium pharaonis; Myrmicinae; Solenopsidini; tramp species